Screening and oenological property analysis of ethanol-tolerant non-Saccharomyces yeasts isolated from Rosa roxburghii Tratt - Li, Yinfeng; Ding, Peipei; Tang, Xiaoyu; Zhu, Wenli; Huang, Mingzheng; Kang, Mei; Liu, Xiaozhu (Frontiers in Microbiology, 2023)
Ethanol tolerance is crucial for the oenological yeasts. Rosa roxburghii Tratt, a Rosaceae plant native to China, is rich in nutritional and medicinal ingredients. In this study, ethanol-tolerant non-Saccharomyces yeasts were screened, and their oenological properties were further evaluated. Three ethanol-tolerant yeast strains (designated as C6, F112, and F15), which could tolerate 12% (v/v) ethanol treatment, were isolated from R. roxburghii, and identified as Candida tropicalis, Pichia guilliermondii, and Wickerhamomyces anomalus, respectively. The winemaking condition tolerances of these ethanol-tolerant yeast strains were similar to those of Saccharomyces cerevisiae X16. However, their growth, sugar metabolic performance and sulphureted hydrogen activities, were different. The β-glucosidase production ability of strain W. anomalus F15 was lower than that of S. cerevisiae X16, and strains of C. tropicalis C6 and P. guilliermondii F112 were similar to S. cerevisiae X16. Electronic sensory properties of the R. roxburghii wines fermented using ethanol-tolerant yeasts together with S. cerevisiae showed no significant differences. However, the mixed inoculation of the ethanol-tolerant yeast strains with S. cerevisiae could regulate the volatile aroma characteristics of the fermented R. roxburghii wine, enriching and enhancing the aroma flavor. Therefore, the selected ethanol-tolerant yeasts have the potential for application in the production of unique R. roxburghii wine.